Control in power electronics : selected problems - Kazmierkowski, Marian P.; Krishnan, R. (Ramu); Blaabjerg, Frede (Academic Press series in engineering., 2002)
The authors were originally brought together to share research and applications through the international Danfoss Professor Programme at Aalborg University in Denmark. Personal computers would be unwieldy and inefficient without power electronic dc supplies. Portable communication devices and computers would also be impractical. High-performance lighting systems, motor controls, and a wide range of industrial controls depend on power electronics. In the near future we can expect strong growth in automotive applications, dc power supplies for communication systems, portable applications, and hi.